Genetic signals of artificial and natural dispersal linked to colonization of South America by non-native Chinook salmon (Oncorhynchus tshawytscha) - Gomez Uchida, Daniel (2018)
Genetics data have provided unprecedented insights into evolutionary aspects of colonization by non-native populations. Yet, our understanding of how artificial (human-mediated) and natural dispersal pathways of non-native individuals influence genetic metrics, evolution of genetic structure, and admixture remains elusive. We capitalize on the widespread colonization of Chinook salmon Oncorhynchus tshawytscha in South America, mediated by both dispersal pathways, to address these issues using data from a panel of polymorphic SNPs. First, genetic diversity and the number of effective breeders (Nb) were higher among artificial than natural populations. Contemporary gene flow was common between adjacent artificial and natural and adjacent natural populations, but uncommon between geographically distant populations. Second, genetic structure revealed four distinct clusters throughout the Chinook salmon distributional range with varying levels of genetic connectivity. Isolation by distance resulted from weak differentiation between adjacent artificial and natural and between natural populations, with strong differentiation between distant Pacific Ocean and Atlantic Ocean populations, which experienced strong genetic drift. Third, genetic mixture analyses revealed the presence of at least six donor geographic regions from North America, some of which likely hybridized as a result of multiple introductions. Relative propagule pressure or the proportion of Chinook salmon propagules introduced from various geographic regions according to government records significantly influenced genetic mixtures for two of three artificial populations. Our findings support a model of colonization in which high-diversity artificial populations established first; some of these populations exhibited significant admixture resulting from propagule pressure. Low-diversity natural populations were likely subsequently founded from a reduced number of individuals.